Recreational Activities and Travel Choices of the Elderly - Putu Ayu Sani Utami; Ni Ketut Guru Prapti (GLOBAL HEALTH SCIENCE GROUP, 2020)
Recreation is a way to get consolation for the elderly. The aim of this study is to analyze recreational activities and travel choices of the elderly who live in Denpasar city, Bali, Indonesia. The study used a descriptive method. The sample consisted of 100 elderly selected by convenience sampling technique. The data was collected by questionare and analyzed using frequency distribution. The results show that even though Bali is a tourist destination and there is an easy access for the elderly who live in the cities, it does not guarantee they come to every tourist spot, seen from most of the elderly (64%) had never done any recreational activities after entering old age. The main obstacle that prevented the elderly from doing recreational activities was taking care of grandchildren (46%). Characteristics of destination locations for elderly travel choices especially have a calm environment (26.9%). The favorite recreation destination is places of worship (63.9%). After recreation, they felt happy and refreshed (88.8%). Recreation can be a fun entertainment for the elderly in their daily routines activities to reduce boredom, but in recreation they should be accompanied by family and pay attention to the characteristics of their favorite tourist spot.